Efeito pró-erétil de uma fração rica em alcalóides isolada de aspidosperma ulei markgr. : estudo in vivo e in vitro - Barros, Adriana Rolim Campos (2005)
The genus Aspidosperma (Apocyanaceae) is known to be rich in yohimbine type of indol alkaloids. This study was aimed to evaluate the alkaloid rich fraction (SF3-5) obtained from Aspidiosperma ulei Markgr. root bark for its general toxicity, behavioral effects in mice and a possible proerectile activity. Acute toxicity tests were performed to determine the LD50 in mice and LC50 with Artemia sp. Behavioral effects were studied in the tests of open-field, hole-board, plus-maze, rota-rod, forded-swimming, and on barbiturate-induced sleeping time. In vitro studies with the fraction were carried out using mouse vas deferens and the rabbit and human corpus cavernous tissues. The estimated values of i.p. LD50 in mice and LC50 with Artemia sp. were in the order of 400 mg/kg, and 3.94 microg/ml, respectively. Behavioral tests in mice revealed a general stimulant activity of SF3-5 on CNS but demonstrated no motor impairment in rota-rod test. At 25 mg/kg intraperitoneal injection of SF3-5, penile erections were evidenced in 75% of the mice. This effect was completely abolished by pretreatment with clonidine (alfa2 –adrenoceptor agonist) or haloperidol (dopaminergic antagonist) and only partially inhibited by L-NAME (nitric oxide synthase inhibitor) and by methylene blue (soluble guanylate cyclase inhibitor). SF3-5 also abrogated the fluoxetine-induced depression in sexual behavior. In mouse vas deferens, contractile effects induced by electrical field stimulation or noradrenaline but not induced by ATP were inhibited by SF3-5 (1-64 microg/ml). In both human and rabbit isolated corpus cavernosum preparations pre-contracted by phenylephrine, high potassium or PGF2alfa, SF3-5 (1-300 microg/ml) caused concentration-dependent relaxation. Our results indicate that SF3-5 manifests pro-erectile activity possibly involving both central (dopaminergic, adrenergic and nitriergic systems) and peripheral (relaxant effect on corpus cavernosal smooth muscle, probably involving Ca+2 flux) mechanisms. These data also suggest that Aspidiosperma ulei Markgr. can be explored as an alternative for the treatment of erectile dysfunction. The study further warrants the identification and isolation of the active chemical compound present in SF3-5, responsible for the pharmacological activity.